2, 2′:6′, 2′′‐Terpyridine Analogues: Structural, Electrochemical, and Photophysical Properties of 2, 6‐Di(thiazol‐2‐yl)pyridine Derivatives. Issue 19 (19th May 2017) - Maroń, Anna; Kula, Slawomir; Szlapa‐Kula, Agata; Świtlicka, Anna; Machura, Barbara; Krompiec, Stanisław; Małecki, Jan Grzegorz; Kruszyński, Rafał; Chrobok, Anna; Schab‐Balcerzak, Ewa; Kotowicz, Sonia; Siwy, Mariola; et al.
Abstract : Several 2, 6‐di(thiazol‐2‐yl)pyridine (dtpy) derivatives substituted at the 4‐position were synthesized, and their structural, photophysical, and electrochemical properties were investigated. The studies proved the attractiveness of this new class of compound as building blocks for materials science, coordination chemistry, and supramolecular chemistry and also revealed the possible tuning of their thermal, photophysical, electrochemical, and electroluminescence properties through the modification of the structure of the substituent. The thermal, photophysical, and electrochemical behavior of the compounds was examined by differential scanning calorimetry (DSC) and for selected compounds by thermogravimetric analysis (TGA), UV/Vis spectroscopy, photoluminescence (PL) spectroscopy, and cyclic voltammetry (CV). Additionally, their selected properties were investigated theoretically by density functional theory (DFT) calculations. The electroluminescence abilities of the synthesized compounds were preliminary tested in host–guest light‐emitting diodes. Abstract : A series of 2, 6‐di(thiazol‐2‐yl)pyridine derivatives are developed as 2, 2′:6′, 2′′‐terpyridine analogues and have prominent properties that could be useful in electroluminescent devices.